The contribution of seed systems to crop and tree diversity in sustainable food systems. - Etten, Jacob van; López Noriega, Isabel; Fadda, Carlo; Thomas, E. (Bioversity International, 2017)
This chapter will review the evidence that shows that farmers’ access to seeds has an impact on the sustainability of food production and consumption. Diverse seeds are needed to support the diversification of agriculture, which in turn may contribute to more diverse diets, and to using species and varieties for the integrity of ecosystem services. In what follows, we define three functions of seed systems. We discuss the evidence that farmers’ seed access influences food production and consumption. We then discuss each of the three key functions (production and distribution, innovation, regulation) in turn and review the evidence that differences in the capacity of seed systems to perform each function make a difference to fulfilling the overall goal of seed systems, in terms of their contribution to sustainable food systems. We also describe existing work to provide data and indicators to characterize each seed system function and assess how these can be used to measure the link between agricultural biodiversity and sustainable food systems in this context.